Performance of polyimide film under hypervelocity impact of micro flyer: Experiments and simulations. (June 2019) - Liu, Tao; Zeng, Zhixin; Zhang, Xinghua; Qiu, Xinming; Cheng, ZhengAi; Wang, Li; Jia, Shaoxia; Cai, Jian
Abstract: The characteristics of polyimide film hypervelocity impacted (HVI) by micro flyer are investigated though experimental and numerical methods. Using the laser driven flyer (LDF) method combined with the technique of scanning electron microscopy (SEM) and explicit dynamics numerical algorithm, the fracture morphology and detailed mechanical responses of polyimide film, both in the impact and non–impact zones, are captured; and a dynamic fracture strain criteria, combing temperature and strain rate, is presented. A parametric study on the performance of polyimide film is implemented and the influence of the factors, including the impact velocity, film thickness, strain rate constant and pre–stress, are assessed. The research reveals that polyimide film exits two failure modes, i.e. ductile punching and brittle cracks. Polyimide materials in the impact zone have experienced a high temperature (>Tg  = 685 K), ultrahigh strain rate (10 8 ∼10 9 ) and plastic state; while in the non–impact zone, it is normal temperature (293–295 K), high strain rate (10 5 ∼10 6 ) and elastic state. Highlights: The fracture morphology of polyimide film under hypervelocity impact is obtained experimentally. The detailed hypervelocity impact response of polyimide film are captured by simulation. A parametric study is implemented and the relating factors are assessed. A dynamic fracture strain criteria for polyimide film is presented.